Harnessing the Transformative Power of Education - Shelley, Becky (Innovations and Controversies: Interrogating Educational Change Ser., 2019)
"The transformative power of education is widely recognised. Yet, harnessing the transformative power of education is complex for exactly those people and communities who would benefit the most. Much scholarship is available describing the ways in which educational access, opportunity and outcomes are unequally distributed; and much scholarship is dedicated to analysing and critiquing the 'problems' of education. This volume gratefully builds on such analysis, to take a more constructive stance: examining how to better enable education to fulfil its promise of transforming lives. Harnessing the Transformative Power of Education returns overall to a broader language of educational change rather than reduce our sense of scale and scope of 'transformation' to what might be measured in or by schools. It offers a series of practical, local but system wide and socially responsible practices, policies and analyses to support the ways that education can work at its best. The projects described here vary in scale and scope but are rooted in a wider sense of community and social responsibility so that education is considered as a necessary sustainable process to ensure productive futures for all. Its contributors include not only scholars, but also professional experts and young people. The book's aim is to share and advance authentic possibilities for enabling all children and young people to flourish through the transformative power of education".